Presence of the relative age effect and its effect on playing time among under-20 players in the Norwegian premier league Tippeligaen - a four-year follow up - Saeter, S. A. (Montenegrin Journal of Sports Science and Medicine, 2016)
European top-level soccer clubs are continually looking for talented players. Few clubs, however, are willing to let youth players play at the highest senior level. Perhaps as a consequence, the search for talented players has resulted in an imbalance in the characteristics of these players, towards an overrepresentation of players born early in the selection year, an effect called the relative age effect (RAE). The RAE has been documented to be present among senior top-level players. Even so, few studies have investigated the effect among youth players at the senior level. The aim of this study is to examine RAE among U17-U20 players in the Norwegian premier league Tippeligaen in the 2009-2012 seasons. Participants were 315 male players born in 1990-1996. The results showed that 68% of the players were born in the two first quartiles of the year. The effect was even increasing in the four-year period. As we could expect based on the literature, the oldest players are given more playing time. However, the connection between playing time and RAE was inconsistent. Norwegian top-level soccer seems to be affected by the RAE when selecting their players. These players are not however guaranteed playing time because of the RAE.